Cowpea Nodules Harbor Non-rhizobial Bacterial Communities that Are Shaped by Soil Type Rather than Plant Genotype - Leite, Jakson; Fischer, Doreen; Rouws, Luc F. M.; Fernandes-Júnior, Paulo I.; Hofmann, Andreas; Kublik, Susanne; Schloter, Michael; Xavier, Gustavo R.; Radl, Viviane (Frontiers in Plant Science, 2017)
Many studies have been pointing to a high diversity of bacteria associated to legume root nodules. Even though most of these bacteria do not form nodules with legumes themselves, it was shown that they might enter infection threads when co-inoculated with rhizobial strains. The aim of this work was to describe the diversity of bacterial communities associated with cowpea (Vigna unguiculata L. Walp) root nodules using 16S rRNA gene amplicon sequencing, regarding the factors plant genotype and soil type. As expected, Bradyrhizobium was the most abundant genus of the detected genera. Furthermore, we found a high bacterial diversity associated to cowpea nodules; OTUs related to the genera Enterobacter, Chryseobacterium, Sphingobacterium and unclassified Enterobacteriacea were the most abundant. The presence of these groups was significantly influenced by the soil type and, to a lesser extent, plant genotype. Interestingly, OTUs assigned to Chryseobacterium were highly abundant, particularly in samples obtained from an Ultisol soil. We confirmed their presence in root nodules and assessed their diversity using a target isolation approach. Though their functional role still needs to be addressed, we postulate that Chryseobacterium strains might help cowpea plant to cope with salt stress in semi-arid regions.